English pronunciation verification system for Apple iOS - Ng, Kelvin Sio Joo. (2013)
Each culture has pronunciation patterns and lilts unique to that culture and these unique elocution styles, while accepted and taken for granted in that culture, can render a word unintelligible in another culture. This calls for an easily accessible application that can quickly give the users affirmation about their pronunciation.